Analysis of the Quality of Human Resources in Providing Public Services at the Nendali Village Office, Jayapura Regency - Randongkir, Lidia Vega; Nurlitasari, Anisa; Koto, Mita; Supriyatno, Budi; Hakim, Azis (Jurnal Indonesia Sosial Sains, 2025)
This research aims to know, describe, and analyze the quality of human resources in the Nendali Village Office, East Sentani District, Jayapura. In this study, the researcher uses the Human Resource Quality Theory that has been adjusted and modified to meet the needs of the research. The researcher applies a qualitative approach because the object of this research involves the activities or actions of individuals or several office officers in carrying out their duties as public servants. Qualitative research methods are used to study the condition of objects naturally, in contrast to experiments, where the researcher plays the role of the main instrument. The data collection technique is carried out through triangulation (method combination), data analysis is inductive/qualitative, and the research results focus on interpretation. Based on the analysis of theories and findings in the field, it can be concluded that the quality of human resources at the Nendali Village Office, East Sentani District, has not fully met the expectations of the community, so improvements are still needed in the future.